FEMORAL SHAFT FRACTURE WITH TOTAL SUPERFICIAL FEMORAL ARTERY AND VEIN RUPTURE FOLLOWING TRACTION MECHANISM TYPE OF INJURY - A CASE REPORT - Emil Simeonov (Peytchinski Publishing, 2024)
The majority of encountered femoral artery lesions are due to penetrating or stab injuries. In cases of closed femoral fractures, artery damages could be missed due to their rarity, as surgeons might not anticipate them on the first encounter with the injured person. Damage Control Orthopaedics (DCO) provides a pathway to managing patients with severe orthopaedic injuries, particularly when the trauma is complicated by vascular injuries, such as femoral artery rupture. The DCO approach prioritizes stabilizing the patient before definitive bone fixation. This way, it provides a stable environment to reconstruct damaged arteries, prevent the secondary inflammatory response, provide hemodynamic stability, and prevent other complications associated with prolonged surgeries. In this case, a 48-year-old man experienced high-energy trauma on his left leg and arrived at the emergency department eight hours after the incident. Upon his arrival, a noticeable deformity was observed in the lower thigh area. X-ray imaging disclosed a distal femoral fracture. Further examination revealed a lack of knee and ankle function, full paraesthesia below the knee region, and absent pedal pulses. Following a CT angiography, a complete rupture of the superficial femoral artery was confirmed. This case was treated with temporary external fixation, femoral artery reconstruction, and prophylactic fasciotomy. External fixation has been later converted to definitive intramedullary fixation.